Inherently Political? Associations of Parent Ethnic–Racial Socialization and Sociopolitical Discussions with Latinx Youths' Emergent Civic Engagement. Issue 1 (26th June 2020) - Pinetta, Bernardette J.; Blanco Martinez, Saraí; Cross, Fernanda Lima; Rivas‐Drake, Deborah
Abstract : Abstract: The current study expands on ethnic–racial socialization (ERS) among Latinx families to include sociopolitical discussions as a way to better understand how these practices relate to adolescents' developmental outcomes, including their ethnic–racial identity (ERI) and their sociopolitical development. More specifically, we examined whether there were direct links between parental ERS practices and sociopolitical discussions at home and adolescents' emergent participatory citizenship via their ERI processes (i.e., exploration and resolution). These questions were examined using path analyses with 267 self‐identified Latinx early adolescents ( M age = 11.88, SD = 1.22; girls = 54.3%). Results revealed direct associations between sociopolitical discussions and cultural socialization at home with civic accountability. Thus, youth whose parents had engaged in more discussions with them about current political issues and who taught them about their ethnic heritage and history endorsed a greater sense of collective responsibility for helping community members in need. Additionally, preparation for bias and sociopolitical discussions at home were each uniquely associated with more ERI exploration, and each was also indirectly associated with expectations for future community involvement via youths' ERI exploration. Our findings come at a critical juncture in time, providing insight into ways we can support the positive ERI development and build the civic capacity of Latinx adolescents. Highlights: More sociopolitical discussions and cultural socialization were linked to more collective responsibility. More sociopolitical discussions were associated with future expectations for community involvement. We found an indirect link between sociopolitical discussions and future expectations via ERI exploration. We found an indirect link between preparation for bias messages and future expectations via ERI exploration. We found a correlation between sociopolitical discussions and cultural socialization.